Portfolio Choice Problems An Introductory Survey of Single and Multiperiod Models - Chapados, Nicolas (SpringerBriefs in Electrical and Computer Engineering, 2011)
This brief offers a broad, yet concise, coverage of portfolio choice, containing both application-oriented and academic results, along with abundant pointers to the literature for further study. It cuts through many strands of the subject, presenting not only the classical results from financial economics but also approaches originating from information theory, machine learning and operations research. This compact treatment of the topic will be valuable to students entering the field, as well as practitioners looking for a broad coverage of the topic.